PENGARUH FASILITAS FISIK DAN FASILITAS NON FISIK TERHADAP KEPUASAN PELANGGAN DI PASAR JBBC MEDAN JOHOR - Muhammad Zuardi (Jurnal Riset AKuntansi dan Bisnis, 2016)
The decreasing number of consumers are becoming a major factor sluggishness traditional market competitiveness . Some of the main reasons customers make the shift from traditional markets to modern markets among others , the existence of the decline of traditional markets is not entirely due to the modern market . Due to the fact that the declining traditional market turnover is also influenced by the availability of facilities given to the buyer . The facility consists of a non- physical facilities and physical facilities . The purpose of this study was to determine the influence of physical facilities and non-physical facilities to customer satisfaction in Pasar JBBC Medan Johor , and analyze the most dominant factor influencing customer satisfaction of shopping at Pasar JBBC Medan Johor. By using multiple regression analysis , the result showed that non- physical facilities and physical facilities of 54.8 % impact on customer satisfaction shopping at Pasar JBBC Medan Johor , while 45.2 % influenced by other factors not examined in this study . Factors of physical facilities provide the most dominant influence on customer satisfaction Market shopping at Pasar JBBC Medan Johor . Security during and after shopping , the air around the hot market , odorless , neat arrangement of goods as well as the friendliness of the seller into the factors affecting shopping convenience.